The Real Effects of Asset Market Bubbles: Loan- and Firm-Level Evidence of a Lending Channel - Jie Gan (Review of Financial Studies, 2007)
[This article studies how a shock to the financial health of banks, caused by a decline in the asset markets, affects the real economy. The land market collapse in Japan provides an ideal testing field in separating the impact of a loan supply shock from demand shocks. I find that banks with greater real estate exposure have to reduce lending. Firms' investment and market valuation are negatively associated with their top lender's real estate exposure. The lending channel is economically important: it accounts for one-third of lending contraction, one-fifth of the decline in investment, and a quarter of value loss.]